PENERAPAN ALGORITMA GENETIKA DALAM PENJADWALAN MATA KULIAH - ,; , (Jurnal Mahasiswa Aplikasi Teknologi Komputer dan Informasi (JMApTeKsi), 2023)
Pelita Indonesia Institute of Business and Technology Pekanbaru has classic scheduling problems. These include a binding schedule, a limited number of lecturers, and certain parameters. The schedule creation process is still done manually and does not yet have an optimization model using a computer application. In order to prepare a good schedule, correlation must be carried out between these components so that there are no cases of schedule collisions. In this research, a Genetic Algorithm approach was carried out to the problems of course scheduling. The application that has been created can determibe scheduling at Pelita Indonesia Institute of Business and Technology throught the application of a genetic algorithm using three main variables, namely lecture data, session time, and lecture hall data. Through Black Box Testing, it can be seen that the application is running as expected and can be said to be feasible in scheduling courses.